2021
DOI: 10.1021/acsanm.0c02782
|View full text |Cite
|
Sign up to set email alerts
|

Shape Effect of Zinc-Tin Oxide Nanostructures on Photodegradation of Methylene Blue and Rhodamine B under UV and Visible Light

Abstract: Water pollutants are currently a major concern, demanding for simple processes for water treatment, photocatalysis being one of the most efficient and promising processes. Metal oxide materials are being widely studied for this application, due to their wide band gaps, with nanostructures being particularly interesting because of their high surface-to-volume ratio. In this context, zinc-tin oxide (ZTO) nanostructures are quite appealing owing to the multiplicity of structures and morphologies possible to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 73 publications
3
16
0
Order By: Relevance
“…According to the tangent of the diagram, the band gaps of ZTO NWs and 3 at% Ag-ZTO NWs were 4.05 and 4.04 eV, which are close to the previously reported value (3.92 eV). The wider band gap for the ZTO NWs may be attributed to their smaller sizes [ 14 ]. The similar absorption edges before and after Ag modification indicate that their bandgap energy difference is negligible [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the tangent of the diagram, the band gaps of ZTO NWs and 3 at% Ag-ZTO NWs were 4.05 and 4.04 eV, which are close to the previously reported value (3.92 eV). The wider band gap for the ZTO NWs may be attributed to their smaller sizes [ 14 ]. The similar absorption edges before and after Ag modification indicate that their bandgap energy difference is negligible [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ternary metals have higher chemical stability as compared to binary metal oxides. ZTO nanostructures have been fabricated for various important applications, including optical sensors [ 6 , 7 ], gas sensors [ 8 , 9 ], dye-sensitized solar cells [ 10 , 11 ] and photocatalysts [ 12 , 13 , 14 ]. In the past few years, different techniques have been applied in synthesizing one-dimensional ZTO nanostructures, including the hydrothermal method [ 15 , 16 ], CVD [ 7 , 17 ] and the template method [ 18 ], among which CVD is the best choice since it is more economical and environmentally friendly [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RhB •+ cation radicals can also be further decomposed into N-deethylated products by hydrolysis or by reacting with HO 2 • / O 2 •− radicals. The resulting N-deethylated products are responsible for a gradual hypsochromic shift in the absorbance peak since the N-deethylation of RhB is known to be a stepwise process [ 77 , 78 , 127 , 128 ]. This hypsochromic shift in the absorbance peak was not observed in Figure 5 a, suggesting that the degradation of RhB through sunlight photocatalysis by the porous ZnO nanostructures is the predominant degradation route in these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported the use of metal oxide materials in the photocatalytic degradation of organic contaminants/dyes [19,34,37,38,[71][72][73][74]. However, their photocatalytic performance strongly depends on the crystal structure, morphology, elemental composition, crystalline phase, exposed surface facets, intrinsic defects (such as oxygen vacancies), lattice distortions, and doping, among others [75][76][77].…”
Section: Metal Oxide Nanostructures and Thin Filmsmentioning
confidence: 99%
“…Moreover, it is largely known that materials' properties are enhanced at the nanoscale level when compared to bulk counterparts [79]. For that reason, the surface-to-volume ratio of metal oxides is highly increased at the nanoscale, and more active sites on their surface are available for organic molecules to interact, leading to higher overall adsorption capacity and enhanced photocatalytic performance in environmental remediation [35,74].…”
Section: Metal Oxide Nanostructures and Thin Filmsmentioning
confidence: 99%